PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS PROBLEM BASED LEARNING PADA MATERI BILANGAN DI KELAS VII SMP NEGERI 22 KOTA JAMBI - Sri Yulia; Buyung Buyung; Relawati Relawati (Universitas Batanghari Jambi, 2018)
Abstract: Products developed in the form of Student Worksheet (LKS) mathematics on the number material for SMP class VII with problem based learning model. The development model used is the ADDIE model consists of several stages: Analyze, Design, Development, Implementation, and Evaluation. Validation was done by 2 material experts, design experts and media experts. The Student Working Sheet (LKS) developed was tested in 3 stages, one to one learner with 3 subjects, small group trial try-out) with the subject of 6 students, field trial (field try-out) with the subject of 36 students. The results showed that the Student Worksheet (LKS) problem based on problem based learning based on the assessment: 1) the material experts obtained the average total of 3.98 included in the category of